Functional Assessment of the Stomatognathic System, after the Treatment of Edentulous Patients, with Different Methods of Establishing the Centric Relation - Aleksandra Nitecka-Buchta; Thomas Proba; Paulina Proba; Kamil Stefański; Stefan Baron (Pain Research and Management)
The study compares subjective experiences of patients, wearing complete dentures. Two different methods of determining a centric relation were performed: the traditional method using wax occlusal rims and the Gerber method, based on gothic arch tracings. The success rate of establishing a centric relation in both methods was evaluated (rentgenodiagnostics). The influence of the method used to obtain the centric relation on patients’ stomatognathic system (condyle centralization, pain) was also evaluated. Better results were achieved in gothic arch tracing method. Before every prosthetic treatment of edentulous patients, a functional analysis of the TMJ is necessary. The lack of centric relation, in a long term adaptation patients, does not lead to TMD symptoms. This trial is registered with NCT03343015.